Main Financial and Economic Functions of Church Elders and Awarding for Their Performancein Tobolsk Diocese in 19th - Early 20th Centuries - A. V. Spichak (Научный диалог, 2018)
The author, based on the content of legislative acts regulating the activities of the Russian Orthodox Church, archival documents, as well as interpretations of modern scientists, presented the range of responsibilities, the main financial and economic functions and the process of awarding Church elders in the 19th - early 20th centuries. The article reveals the conditions for receiving various awards by Church elders and the documents accompanying the procedure of their awarding, preserved in Tobolsk state archive. As the cases of the Tobolsk State archive can show, Church elders were awarded with medals and commendable leaves; moreover, different institutions could express gratitude to them. A study of archive cases showed that the initiating documents in the cases on awarding the Church elders were the petitions of the Church elders, deans’ reports or letters of institutions, for example, a letter of the ataman of the Siberian Cossack troops if the elder served in the prison Church. Archival materials indicate the presence in the 19th - early 20th centuries of the established procedure for awarding Church elders, consisting of 17 stages, which began most often with the petition of Church elders or deans’ reports and ended with a response report of a dean, who accompanied the fee for the award.